2019
DOI: 10.1177/1545968319850138
|View full text |Cite
|
Sign up to set email alerts
|

Differential Poststroke Motor Recovery in an Arm Versus Hand Muscle in the Absence of Motor Evoked Potentials

Abstract: Background. After stroke, recovery of movement in proximal and distal upper extremity (UE) muscles appears to follow different time courses, suggesting differences in their neural substrates. Objective. We sought to determine if presence or absence of motor evoked potentials (MEPs) differentially influences recovery of volitional contraction and strength in an arm muscle versus an intrinsic hand muscle. We also related MEP status to recovery of proximal and distal interjoint coordination and movement fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 63 publications
2
44
0
8
Order By: Relevance
“…This study was more recently followed by another investigation demonstrating the reliance of finger individuation recovery on the presence of motorevoked potentials in the hand. 56 Based on these observations, we speculate that the residual CST of the ipsilesional side was most likely involved in the finger individuation recovery observed in our study. The multifinger motor action during the chord/pianolike training task resembles to some extent the action performed during music playing on a piano.…”
Section: Discussionsupporting
confidence: 60%
“…This study was more recently followed by another investigation demonstrating the reliance of finger individuation recovery on the presence of motorevoked potentials in the hand. 56 Based on these observations, we speculate that the residual CST of the ipsilesional side was most likely involved in the finger individuation recovery observed in our study. The multifinger motor action during the chord/pianolike training task resembles to some extent the action performed during music playing on a piano.…”
Section: Discussionsupporting
confidence: 60%
“…These findings are in line with results from other studies that described recovery of proximal joint movements preceding recovery of distal movements, suggesting differences in neural substrates for paretic upper limb recovery. 22 , 34 , 35 In our study, the relative infarct size in rats was within the range of relative infarct sizes in stroke patients. Hemispheric infarct volume was about 3% in rats and ranged between 0.1% and 26% in humans.…”
Section: Discussionsupporting
confidence: 71%
“…It is considered that the rTMS treatment improved the FMA score, and the patients with more severe motor paralysis had improved proximal upper limb movements. Schambra et al reported that there was no difference in FME-UE score recovery with or without MEP in patients in the acute phase, but there was less improvement in patients with high FMA scores than in those with low FMA scores, and FMA recovery curves plateaued below the reported normal levels for both the arm and hand (51). The lower response of patients with high motor function compared to moderately paretic patients in our study might be because the treatment-recovery values were low in patients with high motor function.…”
Section: Discussionmentioning
confidence: 97%